Pelatihan Pengelolaan Taman Baca dan Penyuluhan Jajanan Anak yang Sehat dan Aman - Maifitrianti; Nurhasanah; Viviandhari, Daniek (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
This community service activity was carried out in the society-based library blok E, Pasir Angin village, Cileungsi, Jawa Barat. This activity aimed to increase the knowledge and skills of society-based library administrators in managing their society-based library.  Furthermore, a coloring competition for kids and counseling on healthy and safe snacks was also held which aimed to increase public knowledge and at the same time encourage public interest in visiting this society-based library. The training activities were carried out using the discussion method and practice on how to classify books, make catalog cards, book call numbers, and the membership lists of society-based libraries. Counseling activity was carried out using lecture and discussion methods. Evaluation of the training activity was carried out using the interview method, while the counseling activity was evaluated using a questionnaire instrument. The result be achieved from this activity is that the administrators can manage the society-based library well so that they are able to foster public interest in visiting and at the same time stimulate public interest in reading.